2016
DOI: 10.3402/gha.v9.32518
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Fatal road traffic Collisions in Trinidad and Tobago, West Indies (2000–2011)

Abstract: Summary of what was known• Few studies on road traffic collisions conducted in Latin American and the Caribbean region• Increasing car ownership within the region• Lack of seatbelt usage in Trinidad• Most accidents are associated with alcohol usage• High mortality among pedestriansSummary of what this study adds• Most collisions occur at night• Most collisions occur at weekends• Collisions are evenly distributed throughout the year• More males than females die in fatal collisions• The most productive age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…This study indicated that 43.2% of the victims of RTAs were car drivers, in accordance with the study by Gopaul et al (39) in Trinidad. Previous studies conducted in other countries, such as in the Ivory Coast (40), China (41), Russia (42) and Pakistan (43) have reported that pedestrians have a higher incidence of traffic accident mortalities.…”
Section: Age Group (Years) Psychoactive Substancessupporting
confidence: 92%
“…This study indicated that 43.2% of the victims of RTAs were car drivers, in accordance with the study by Gopaul et al (39) in Trinidad. Previous studies conducted in other countries, such as in the Ivory Coast (40), China (41), Russia (42) and Pakistan (43) have reported that pedestrians have a higher incidence of traffic accident mortalities.…”
Section: Age Group (Years) Psychoactive Substancessupporting
confidence: 92%
“…Studies show that most fatalities happen during twilight hours (1). Assessing accident-related factors, such as time intervals, including days, months, and seasons can be effective in reducing road accidents (1). The present study was conducted to investigate factors contributing to fatal road traffic accidents in the south of Kerman during the period from 2013 to 2017.…”
Section: Introductionmentioning
confidence: 98%
“…Road traffic accidents are from among the major causes of deaths worldwide (1). Every year, over 1.2 million people die from road accidents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations